A Complete Modeling and Control for Wind Turbine Based of a Doubly Fed Induction Generator using Direct Power Control - Fawzi Senani; Abederrezak Rahab; Hocine Benalla (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The paper presents the complete modeling and control strategy of variable speed wind turbine system (WTS) driven doubly fed induction generators (DFIG). A back-to-back converter is employed for the power conversion exchanged between DFIG and grid. The wind turbine is operated at the maximum power point tracking (MPPT) mode its maximum efficiency. Direct power control (DPC) based on selecting of the appropriate rotor voltage vectors and the errors of the active and reactive power, the control strategy of rotor side converter combines the technique of MPPT and direct power control. In the control system of the grid side converter the direct power control has been used to maintain a constant DC-Link voltage, and the reactive power is set to 0. Simulations results using MATLAB/SIMULINK are presented and discussed on a 1.5MW DFIG wind generation system demonstrate the effectiveness of the proposed control.